Prevalence and Risk Factors of Undiagnosed Hypertension among Young Professional Educators: A Study Using Updated AHA Guidelines - Purohit, Geetanjali; Sharma, Tanya; Shaikh, Uzma; Sharma, Purva; Shekh, Nuzhat; Shah, Viral; Shukla, Shardha (Medical Science: Trends and Innovations Vol. 2, 2025)
Background: Hypertension or High arterial blood pressure (BP) is a major public health problem and common non-communicable disease. Professional educators are facing various workplace issues, which can aggravate non-communicable diseases like hypertension (HTN). Work pressure, stress, workload, and sedentary lifestyle are major factors reported. Aim: The aim of the study was to assess the prevalence of HTN with new guidelines and its correlation with associated factors in professional educators. Materials and Methods: This cross-sectional study was carried out in 220 professional medical educators in Vadodara city. Data on socio-demographic profiles, different risk factors, and BP were recorded. HTN was recorded according to pre-defined criteria and described by new AHA guidelines. Factors associated with HTN were analyzed by Chi-square test (\(χ\)2). Results: The study found a high prevalence of HTN and identified HTN as a significant health burden for professional educators of Vadodara city. The prevalence of elevated BP among professional educators was approximately 80% as per new AHA guidelines. The mean systolic blood pressure, diastolic blood pressure, mean blood pressure and pulse pressure were found to be 126.73\(±\)6.02, 82.02\(±\)3.02, 96.32\(±\)3.46, and 42.05\(±\)4.99, respectively. HTN was found to be associated with age and body mass index (BMI) (\(χ\)2 P < 0.05). The author also found that 41–50 years of age group BP were found to be elevated in more than 55% of the population. Conclusion: The study found that BP was found to be elevated in more than 50% of subjects even with normal BMI. The study also found that there is no significant difference in males and females for BP indices. The percentage we found for Stage I HTN cannot be ignored even in such a small group. Studies in large groups or longer time are recommended and prevalence data need to be revised for the prevention and management of HTN as per the American Heart Association (AHA) guidelines.